Fake news and misinformation in the era of COVID-19 through social networks - guenchoub, abdelrahman (Journal of Social Sciences and Humanities, 2023)
This study aims to research the flow of information in social networks during the time of Covid 19 and the impact it can have in creating a situation of media disinformation and publishing fakenews in individuals. These sow confusion to face this epidemic and the prevention methods adopted by specialists. To address this issue, we have tried to provide insight into the concepts of disinformation and fakenews. Next, we featured models of fake news about the epidemic that were widely popular among users.